Anti-N-methyl-D-aspartate receptor(NMDAR) antibody encephalitis presents in atypical types and coexists with neuromyelitis optica spectrum disorder or neurosyphilis. Issue 1 (December 2017) - Qin, Kaiyu; Wu, Wenqing; Huang, Yuming; Xu, Dongmei; Zhang, Lei; Zheng, Bowen; Jiang, Meijuan; Kou, Cheng; Gao, Junhua; Li, Wurong; Zhang, Jinglin; Wang, Sumei; et al.
Abstract Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a clinically heterogeneous disorder characterized by epileptic seizures, psychosis, dyskinesia, consciousness impairments, and autonomic instability. Symptoms are always various. Sometimes it presents in milder or incomplete forms. We report 4 cases of anti-NMDAR encephalitis with incomplete forms, 3 cases of which were accompanied by neuromyelitis optica spectrum disorder or neurosyphilis respectively. Case presentation A 33-year-old man presented with dysarthria, movement disorder and occasional seizures. He had 6 relapses in 28 years. When suffered from upper respiratory tract syndrome, he developed behavioral and consciousness impairment. Cranial MRI was normal. Viral PCR studies and oncologic work-up were negative. Anti-NMDAR antibody was detected in CSF and serum. A 21-year-old female manifested dizziness and diplopia ten months and six months before, respectively. Both responded to steroid therapy and improved completely. This time she presented with progressive left limb and facial anesthesia, walking and holding unsteadily. Spinal cord MRI follow-up showed abnormality of medulla oblongata and cervical cord(C1). Anti-AQP4 and anti-NMDAR were positive in CSF. Steroid-pulse therapy ameliorated her symptoms. A 37-year-old male experienced worsening vision. He was confirmed neurosyphilis since the CSF tests for syphilis were positive. Protein was elevated and the oligoclonal IgG bands(OB) and anti-NMDAR was positive in CSF. Anti-aquaporin 4(AQP4) antibodies and NMO-IgG were negative. Cranial MRI showed high FLAIR signal on frontal lobe and low T2 signal adjacent to the right cornu posterious ventriculi lateralis. Treatment for neurosyphlis was commenced with gradual improvement. A 39-year-old male, developed serious behavioral and psychiatric symptoms. Examination showed abnormal pupils and unsteady gait. He was confirmed neurosyphilis according to the CSF tests for syphilis. Anti-NMDAR was positive in CSF and serum. Cranial MRI showed lateral ventricles and the third ventricle enlargement and signal abnormality involving bilateral temporal lobe, corona radiate and centrum semiovale. PenicillinG, pulsed methylprednisolone and intravenous immunoglobulin was administered. He was stable. Conclusion Anti-NMDAR encephalitis can present in atypical types. When relapsing, it may present with partial aspects or with isolated symptoms of the full-blown syndrome. Anti-NMDAR encephalitis may be related to neuromyelitis optica spectrum disorder or neurosyphilis.